Pendampingan Strategi Pemasaran Digital di SMP Muhammadiyah 10 Bungah - Aslamiyah, Suaibatul (JURNAL PENGABDIAN MANAJEMEN, 2025)
Increasingly fierce competition among schools presents a challenge in utilizing digitalization as a medium on the internet that is used for all needs. The purpose of this community service is to help SMP Muhammadiyah 10 Bungah increase the number of students with a wider reach. The community service partner is SMP Muhammadiyah 10 Bungah. The result of this community service activity is an increase in knowledge about digital marketing in schools through marketing media with minimal capital and a marketing mix strategy that offers competitive products; competitive prices; ease of process and others.